Big data driven security collaborative ecological construction - Xuhua BAO; Xiaodong QU; Xinhua ZHENG (大数据)
Big data technology in network security field has brought challenges and opportunities at the same time.New technology and new model spring up with data breaches of privacy risks,cross-border data flows,data misuse and a series of security risks.The idea of big data security to deal with these risks was introduced.At the same time,the development of big data technology has brought great opportunities to the improvement of security industry capacity.Big data technology,intelligent security mode and security industry synergy will be developed.